Gender, male-typicality, and social norms predicting adolescent alcohol intoxication and marijuana use. (October 2015) - Mahalik, James R.; Lombardi, Caitlin McPherran; Sims, Jacqueline; Coley, Rebekah Levine; Lynch, Alicia Doyle
Abstract: Objective: This study examined the direct and interactive effects of gender, male-typicality, and social norms in predicting the initiation and longitudinal patterns of alcohol intoxication and marijuana use in U.S. youth. Method: Data were drawn from a longitudinal survey of 10, 588 youth who participated in the in-home survey of the National Longitudinal Study of Adolescent Health (Add Health). Multilevel growth modeling used data from three time points to assess trajectories of substance use from adolescence to young adulthood. Results: Analyses indicated that gender, male-typicality, as well as home availability, friend social norms, and schoolmate social norms predicted initial levels of intoxication and marijuana use, with gender, friend norms, and schoolmate norms also predicting differential rates of growth over time in intoxication and marijuana use. Interaction results indicated that gender moderated male-typicality's relationship to both substance use variables, and home availability's relationship to alcohol intoxication. Conclusions: These findings extend the literatures regarding interrelations among gender, gender roles, social norms, and health risk behaviors by (a) locating the genesis of those effects in adolescence, (b) identifying gender and social norms to be salient in terms of both initiation and growth of substance use over time, (c) suggesting that gender differences should be understood as moderated by other social-contextual variables, and (d) arguing that prevention efforts should address gender and gender roles more explicitly in programming. Highlights: Adolescent males drink more and increase use of substances faster than females. Male-typicality predicted higher alcohol and marijuana use for males and females. Social norms predicted alcohol and marijuana use. Male-typical males were most at risk for substance abuse. Alcohol in the home was a risk for female intoxication.